2018
DOI: 10.1186/s40352-018-0079-0
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to implementing an urban co-responding police-mental health team

Abstract: BackgroundIn an effort to reduce the increasing number of persons with mental illness (PMI) experiencing incarceration, co-responding police-mental health teams are being utilized as a way to divert PMI from the criminal justice system. Co-response teams are typically an inter-agency collaboration between police and mental health professionals, and in some cases include emergency medical personnel. These teams are intended to facilitate emergency response by linking patients to mental health resources rather t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 20 publications
1
42
0
Order By: Relevance
“…Those already in recovery may require an updated relapse prevention plan to keep focused on long-term goals. For clients wanting to discontinue substance use, knowledge of withdrawal management, outpatient services, and treatment options is essential (Bailey et al, 2018 ). Since March 2020, many rehabilitation programs have slowed or moved online to prevent the spread of COVID-19, requiring workers to maintain viable service partnerships and up-to-date awareness of referral processes to effectively connect marginalized clients with the programs they need to survive (Armstrong, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Those already in recovery may require an updated relapse prevention plan to keep focused on long-term goals. For clients wanting to discontinue substance use, knowledge of withdrawal management, outpatient services, and treatment options is essential (Bailey et al, 2018 ). Since March 2020, many rehabilitation programs have slowed or moved online to prevent the spread of COVID-19, requiring workers to maintain viable service partnerships and up-to-date awareness of referral processes to effectively connect marginalized clients with the programs they need to survive (Armstrong, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Outcome studies evaluating the efficacy of MCITs are scarce, though the few available studies show promising results (Bailey et al, 2018 ; Blais et al, 2020 ; Kirst et al, 2015 ; Kisely et al, 2010 ; Lamanna et al, 2015 ; Semple et al, 2020 ). A systematic review found co-responder crisis models can reduce the number of mental health act apprehensions and use of police custody for people with mental illness (Puntis et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to CIT, a number of jurisdictions have implemented mental health courts which aim to improve adherence to treatment as a means of avoiding incarceration (Kuehn, 2007); however, these courts are not able to serve all individuals with a mental illness who enter the justice system. More recently, jurisdictions have implemented diversion programs for individuals with mental health (Bailey et al, 2018) conditions or SUD (Collins, Lonczak, & Clifasefi, 2017) who commit low level, non-violent offenses; diversion is a way to link individuals to appropriate services and to medical professionals and has been shown to reduce repeat arrests. Programs like Seattle's Law Enforcement Assisted Diversion, which diverts individuals into supportive case management programs instead of jail, have reduced subsequent arrests by nearly 60% for individuals involved in low-level drug and prostitution activity (Collins et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, prior research has relied on different definitions to identify individuals who have frequent contact with the justice system, taking into account only arrests for a protective hold (Akins et al, 2016), or only jail or incarcerated individuals (Baillargeon et al, 2009;Hwang et al, n.d.;Kopak, Guston, Maness, & Hoffmann, 2019;White et al, 2006), or only anecdotal evidence from police departments or news media (Santos & Goode, 2014). Given the limited samples used in prior studies, the true prevalence of mental illness and SUD among repeat arrestees is unknown (Bailey et al, 2018). This is problematic as repeat arrestees are typically presumed to be living with a mental illness (Akins et al, 2016).…”
Section: Introductionmentioning
confidence: 99%